Stress-Strain and Strength Behavior of Undrained Organic Soil in Kupondol, Kathmandu - Khadka, Padma Bahadur (Journal of the Institute of Engineering, 2011)
The Kathmandu valley is mostly composed of an organic layer locally known as Kalimati, meaning black soil in Nepali. In spite of the unsuitability of organic soil as foundation subsoil, due to its high compressibility and low strength, many civil engineering structures (i.e. residential buildings and high-rise commercial buildings) are being built at an alarming rate. Even more alarming is the fact that no systematic and comprehensive studies have ever been conducted on the geotechnical properties of this highly problematic soil deposit. Geotechnical investigations that have been performed for construction projects, including those structures whose foundation lies on Kalimati soil, typically contain data on general properties of the soil and only to some extend the consolidation and the shear parameter obtained from unconfined compression tests and direct shear tests. As the local name indicates, these soils are black in color, having a high water content and high liquid limit and they are hard when dry but soft when wet. The organic soil is found at different depths and different thicknesses. Sometimes it exists too deep to have a significant effect on the foundation. In many areas it exists at a shallow depth with significant thickness, thus having considerable effect on the foundation of the structure above it. While existing data provides useful information for the design of foundations, almost no data exists on the undrained behavior of the soil, which foundation design on this type of soil should be based on. There is a serious need for research work related to behavior of undrained organic soil deposits in the Kathmandu. Specifically pore pressure, shear strength and stress-strain characteristics, especially under triaxial compression. Key Words: Organic deposit; Foundation; Engineering properties; Kalimati; Geotechnical investigation DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5101 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 113-118 Uploaded Date: 20 July, 2011